Cardiovascular safety profile of taxanes and vinca alkaloids: 30 years FDA registry experience. Issue 2 (24th December 2021) - Batra, Akshee; Patel, Brijesh; Addison, Daniel; Baldassarre, Lauren A; Desai, Nihar; Weintraub, Neal; Deswal, Anita; Hussain, Zeeshan; Brown, Sherry-Ann; Ganatra, Sarju; Agarwala, Vivek; Parikh, Purvish M; et al.
Abstract : Objective: Antimicrotubular agents are among the most commonly used classes of chemotherapeutic agents, but the risk of cardiovascular adverse events (CVAEs) remains unclear. Our objective was to study the CVAEs associated with antimicrotubular agents. Methods: The Food and Drug Administration's Adverse Event Reporting System was used to study CVAEs in adults from 1990 to 2020. Reported single-agent (only taxane or vinca alkaloid) CVAEs were compared with combination therapy (with at least one of the four major cardiotoxic drugs: anthracycline, HER2Neu inhibitors, tyrosine kinase inhibitors and checkpoint inhibitors) using adjusted polytomous logistic regression. Results: Over 30 years, 134 398 adverse events were reported, of which 18 426 (13.4%) were CVAEs, with 74.1% due to taxanes and 25.9% due to vinca alkaloids. In 30 years, there has been a reduction in the proportion of reported CVAEs for taxanes from 15% to 11.8% (Cochran-Armitage P-trends <0.001) with no significant change in the proportion of reported CVAEs for vinca alkaloids (9.2%–11.7%; P-trends=0.06). The proportion of reported CVAEs was lower in both taxane and vinca alkaloid monotherapy versus combination therapy (reporting OR=0.50 and 0.55, respectively). Anthracyclines and HER2Neu inhibitor combinations with taxanes or vinca alkaloids primarily drove the higher burden of combination CVAEs. Hypertension requiring hospitalisation and heart failure was significantly lower in monotherapy versus combination antimicrotubular agent therapy. Conclusions: Antimicrotubular agents are associated with CVAEs, especially in combination chemotherapy regimens. Based on this study, we suggest routine cardiovascular assessment of patients with cancer before initiating antimicrotubular agents in combination therapy.